Microbial exopolysaccharides for immune enhancement: Fermentation, modifications and bioactivities. (June 2020) - Chaisuwan, Worraprat; Jantanasakulwong, Kittisak; Wangtueai, Sutee; Phimolsiripol, Yuthana; Chaiyaso, Thanongsak; Techapun, Charin; Phongthai, Suphat; You, SangGuan; Regenstein, Joe M.; Seesuriyachan, Phisit
Abstract: Many microorganisms are able to synthesize polysaccharides and then secrete them into the external environment; these compounds are known as exopolysaccharides (EPS). The EPS are produced for various purposes including protection, adhesion, biofilm formation, and as a nutrient source. These polymers can be produced by microbes such as archaea, bacteria, and fungi. On an industrial scale, it is beneficial to use microbes because they can be cultivated using controlled conditions and produce a large quantity of EPS within short periods. Fermentation techniques, therefore, are important strategies that are used to improve product yield and productivity. These techniques can be done using submerged fermentation and solid-state fermentation. In addition, the application of optimization techniques are able to be used to obtain the maximum yield of microbial EPS. Some EPS (called bioactive EPS) derived from microbes show bioactivities such as anticancer, antioxidant, antimicrobial, and immunomodulatory activities. There are many factors influencing their bioactivities including their structure, molecular weight, functional groups, and monosaccharide compositions. Moreover, there are many reports where various methods have been used to modify microbial EPS to improve their bioactivities. The modification methods include biological, physical, chemical, and biomolecular modifications. Additionally, immunomodulatory EPS have been extensively studied. The immune stimulating activities of EPS have been investigated both in vitro and in vivo, and some reports have suggested possible pathways for activating the immune response. This review will focus on resources, fermentation, modification, and bioactivities of EPS, and review possible mechanisms of microbial EPS stimulating immune responses. Graphical abstract: Image 1 Highlights: Microbial exopolysaccharides exhibit various biological activities. Structural modifications can improve bioactivities of exopolysaccharides. Immunomodulatory exopolysaccharides activate the immune system via NF-кB and MAPK pathways. Microbial exopolysaccharides have a prebiotic property and modulate the immune system.